(untitled) (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2019)
Public services become one of the needs of the community that must be met by local or central government, such as. Dlingo Village Government which has innovation in doing public service that is with Village Information System (SID) that can give information fast and precisely related Information about public service, besides information about Dlingo Village. This study aims to determine the Village Information System in public service in Dlingo Village, Dlingo District, Bantul Regency. This research uses descriptive research type and qualitative method. The results of this study were obtained from Dlingo Village Government as the public service implementer and Dlingo Village community as the recipient of public service. , proved that the services provided by the Dlingo Village government have been effective and fast.